Detection of Intrusions in Internet of Things Based Deep Auto Encoder Using Deepnets - Atlas, L. Godlin; Shiny, K.V.; Arjun, K.P.; Sreenarayanan, N.M.; Nithiya, J. Lethisia (International Journal of Sensors Wireless Communications and Control, 2024)
<span class=
Keywords: Detection